Liver Function Test Parameters in Hypothyroid Patients Visiting Tertiary Care Center of Western Nepal: A Cross-Sectional Study - Tamang, Binaya; Harijan, Krishnadatt; Pokhrel, Buddhi Raj; Karki, Manoj; Shrestha, Jharana; Gautam, Narayan; Sharma, Binit Kumar; Yadav, Tapeshwar; Sah, Sanjay Kumar (Med Phoenix, 2023)
Introduction: Due to the complicated interactions between the thyroid gland and liver, thyroid hormone dysfunction may affect the liver function tests, and could be of clinical importance. We aimed to compare the hepatic function parameters between hypothyroid and euthyroid patients visiting tertiary care center of western Nepal.Materials and Methods: This hospital-based cross-sectional study was conducted among 113 hypothyroid and 111 euthyroid patients. After consent, thyroid function and liver function parameters were analyzed using automated analyzers. Mann-Whitney U test, Spearman’s correlation, and multiple linear regression analysis were performed for analysis. A p-value of